“Mama Papua Berencana”: Women’s Empowerment Toward Healthy and Quality Families - Novila Hardiana Utami; Siswanto Pabidang; Lidia Febriyanti (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2026)
The low participation of indigenous Papuan mothers in Family Planning (FP) programs remains a significant public health concern, influenced by cultural factors, limited health literacy, and restricted access to information. The perception that having many children symbolizes family strength leads some communities to view FP programs as a form of limiting reproduction that conflicts with traditional values. This community service initiative aims to improve the knowledge, attitudes, and perceptions of indigenous Papuan mothers regarding the importance of family planning through culturally grounded health education. The methods employed included interactive counseling sessions, myth clarification discussions, administration of pretest–posttest questionnaires, and the distribution of educational booklets. The activity was conducted among 30 women of reproductive age (WRA) in Doyo Baru Village, Jayapura Regency. The results demonstrated significant improvements in knowledge (p = 0.000), attitudes (p = 0.000), and perceptions (p < 0.001) following the intervention. The proportion of participants with good knowledge increased from 26.7% to 86.7%, positive attitudes increased to 100%, and positive perceptions rose to 90%. This initiative proved effective in enhancing mothers’ readiness to consider the use of modern contraceptives through a contextual and participatory educational approach. It is recommended that similar programs be implemented sustainably, involving community health cadres and local leaders to strengthen social support for FP programs.